Post concussion syndrome after mild traumatic brain injury in a single neurosurgical center in east coast, Malaysia - Buveinthiran Balakrishnan (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Mild traumatic brain injury is the most common form of traumatic brain injury. Individuals sustaining mild head injuries often complain of a cluster of symptoms termed post concussion syndrome. Post concussion syndrome can be profoundly disabling. The study aims to determine the prevalence of post concussion syndrome in an adult population with mild traumatic brain injury in a single neurosurgical center in East Coast, Malaysia. To determine the duration of symptoms and factors associated with post concussion syndrome in adult population with mild traumatic brain injury in a single neurosurgical center in East Coast, Malaysia. The study adopts Cross Sectional study, in a single neurosurgical center in Kuantan, Pahang. Study period is from January 2016 – December 2016. Universal sampling method was used, all patients with mild traumatic brain injury presenting to HTAA, meeting the inclusion and exclusion criteria is included in this study. Patients are then subjected to the checklist for diagnosis of post concussion syndrome as per ICD 10 classification at 2 weeks interval. Between February 2016 – December 2016, a total of 209 patients with mild traumatic injury have been recruited to this study. Road traffic accidents were the main mechanism of injury among 83.7% subjects, while the remaining were attributed to falls (8.6%), assault (5.7%) and sports based injury, which accounts for 1.9%. Median age of the study subjects was 22 (IQR=18.0). Majority, 63.6% of the study subjects were male. More than 80% (80.9%) of the subjects were Malay, followed by Chinese (12.0%), Indian (4.8%), and the least were from other races (2.4%). The prevalence of post concussion syndrome for 2 weeks, 3 months and 6 months since injuries were 9.6%, 8.1% and 8.1% respectively. Based on the results however, none of variables tested showed up as significant predictors for post concussion syndrome. Majority of individuals who sustain mild traumatic brain injuries are young adults, and the most common cause is road traffic accidents. Less than 10% of patients with mild traumatic brain injury had post concussion syndrome after 6 months following trauma. Further studies is required to determine significant predictors for post concussion syndrome.